2022
DOI: 10.4081/ripppo.2022.583
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapeutic change in children and adolescents who have been sexually abused: a model from participants’ perspectives

Abstract: Introduction: Change in psychotherapy research in cases of child sexual abuse (CSA) has mainly emerged from a symptomatologic view, which needs to be complemented by a subjective perspective of change. Thus, this article aim is to describe different outcomes and stages of change during psychotherapy in children and adolescents who have been sexually abused, from the subjective perspectives of those involved in the process. Methods: A longitudinal qualitative study was developed. Qualitative interviews were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Qualitative studies to date have identified a number of important themes that contribute to the knowledge base on young people's experiences of therapy following sexual abuse. Children's and young people's anxieties about attending therapy and not knowing what to expect from therapy have been documented (Capella et al, 2016(Capella et al, , 2018a(Capella et al, , 2022Dittman & Jensen, 2014;Foster & Hagedorn, 2014); the importance of young people feeling safe and building trust in the therapist (Jensen et al, 2010) as someone who understood and had expertise in this field (Dittman & Jensen, 2010); the value of talking about the abuse experience (Capella et al, 2016) and being able to do this without feeling overwhelmed (Dittman & Jensen, 2010), while at the same time not feeling pressured to talk about it (Visser & DuPlessis, 2015); and getting help with managing symptoms of distress, leading to general improvements in wellbeing (Beiza et al, 2015;Jessiman et al, 2016;Capella et al, 2018a). Finally, young people have described their journey through therapy and the changes they experienced, seeing themselves in a more positive light, as stronger, more reflective and reliant on themselves (Beiza et al, 2015;Capella et al, 2016;2018a;2018bJessiman et al, 2016).…”
Section: N O N -C O M M E R C I a L U S E O N L Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies to date have identified a number of important themes that contribute to the knowledge base on young people's experiences of therapy following sexual abuse. Children's and young people's anxieties about attending therapy and not knowing what to expect from therapy have been documented (Capella et al, 2016(Capella et al, , 2018a(Capella et al, , 2022Dittman & Jensen, 2014;Foster & Hagedorn, 2014); the importance of young people feeling safe and building trust in the therapist (Jensen et al, 2010) as someone who understood and had expertise in this field (Dittman & Jensen, 2010); the value of talking about the abuse experience (Capella et al, 2016) and being able to do this without feeling overwhelmed (Dittman & Jensen, 2010), while at the same time not feeling pressured to talk about it (Visser & DuPlessis, 2015); and getting help with managing symptoms of distress, leading to general improvements in wellbeing (Beiza et al, 2015;Jessiman et al, 2016;Capella et al, 2018a). Finally, young people have described their journey through therapy and the changes they experienced, seeing themselves in a more positive light, as stronger, more reflective and reliant on themselves (Beiza et al, 2015;Capella et al, 2016;2018a;2018bJessiman et al, 2016).…”
Section: N O N -C O M M E R C I a L U S E O N L Ymentioning
confidence: 99%
“…Finally, young people have described their journey through therapy and the changes they experienced, seeing themselves in a more positive light, as stronger, more reflective and reliant on themselves (Beiza et al, 2015;Capella et al, 2016;2018a;2018bJessiman et al, 2016). The therapeutic relationship and the support experienced from parents, peer groups and other support networks were seen as core to psychotherapeutic change (Capella et al, 2022). More studies are needed that consult with young people directly about their experiences of therapy (Capella et al, 2022), drawing on samples from different contexts, to test the trustworthiness, credibility and relevance of these findings for adolescents who have experienced sexual abuse.…”
Section: N O N -C O M M E R C I a L U S E O N L Ymentioning
confidence: 99%
“…Cooper ( 2018 ) recognizes goals as an effective way to implement the idiographic approach in the context of counseling, and recent meta-analyses support this positive effect (Epton et al ., 2017 ; Harkin et al ., 2016 ; Zarzycka et al ., 2022 ; Capella et al ., 2022 ). In fact, an idiographic approach gives access to the client’s progress and to complex processes of change in psychotherapeutic work, addressing aspects that reflect the individuality of each client and the progress in overcoming specific difficulties and problems.…”
Section: Introductionmentioning
confidence: 99%
“…Personal Projects Analysis (PPA, Little, 1983 ; Little & Balsari- Palsule, 2020 ) is a cognitive-motivational approach that allows access to the personal goals that people formulate and try to achieve. Since its formulation, numerous potentialities of its use in counseling and psychotherapy context as an idiographic approach have been claimed (Little, 2011 ; Little & Chambers, 2004 ; Capella et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Just as the subjective experience of the clinician, enriched by reflection, training, and the use of qualitativequantitative measures, can be of great help in the therapeutic process, in the same way the investigation into the subjective experience of the young patient or parent can become a central aspect of the therapeutic alliance and subjective change process. Attention to the subjective perspective in the therapeutic process can provide important information for understanding the mechanisms of change in particularly vulnerable clinical populations such as children and adolescents who have been sexually abused (Capella et al ., 2022 ), but it can also foster change itself through child-therapist or parent-therapist relationship (Nunez et al ., 2022). Giving a voice to the child’s experience and the perception of his/her own well-being, as a verification of the effectiveness of the treatment, can be of great use especially in understanding how much parent and child are able to cooperate in achieving therapeutic goals starting from the understanding of suffering (Abraham, Edginton, Cottrell, & Tubeuf, 2022 ).…”
mentioning
confidence: 99%